2013
DOI: 10.1016/j.rinim.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of autoantibodies and specific antibodies in response to influenza virus vaccination in physically active older individuals

Abstract: Immunosenescence is associated to aging and among many changes in immune response is reported a reduced response to vaccination and an increase in the number of cases of autoimmunity, caused by autoantibodies known as natural antibodies whose function, according to reports, would be protection against infection and inflammation. Although immunosenescence is an irreversible process, regular moderate exercise can attenuate some aspects of the decline in the immune system. So, the aim of this study was to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 26 publications
4
64
2
2
Order By: Relevance
“…Thirty women who practiced a regular exercise training program for 1.5 to 5 years and 30 sedentary women, all volunteers, participated in the study, which the Federal University of São Paulo Paulista School of Medicine ethics committee approved. The training protocol that the exercisers performed has been previously described . Sedentary subjects were independent and active but had not practiced regular physical exercise for at least 5 years.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty women who practiced a regular exercise training program for 1.5 to 5 years and 30 sedentary women, all volunteers, participated in the study, which the Federal University of São Paulo Paulista School of Medicine ethics committee approved. The training protocol that the exercisers performed has been previously described . Sedentary subjects were independent and active but had not practiced regular physical exercise for at least 5 years.…”
Section: Methodsmentioning
confidence: 99%
“…In older adults, those classified as more active show greater antibody responses than their more sedentary counterparts [90, 91]. Data from randomized interventional trials support a causal effect in this relationship.…”
Section: Interventions To Improve Antibody Responses To Vaccinationmentioning
confidence: 99%
“…It has also been suggested that these findings have important implications to understand the use of IL-7 and IL-15 as adjuvant for therapeutic vaccination protocols against intracellular pathogens, considering that CD8 + T cells constitute a critical component of protective immunity (Bhadra et al, 2010). Recently, previous regular physical exercise has provided to be an adjuvant in vaccination (Bachi et al, 2013). Besides, it can improve the life quality during the aging process and extend life span (Handschin and Spiegelman, 2008).…”
Section: Discussionmentioning
confidence: 99%